Philosophy as a Way of Life: A Comparative Study of the Confucian Notion of Harmony (he). - Luque-Moya, Gloria (Central European Pragmatist Forum, 2022)
Confucian philosophy has recently attracted growing interest from academics, because this model of thought can make valuable contributions to the articulation of our present world. Nevertheless, most of this research has described Confucius as a moral philosopher and has addressed the potential of this tradition exclusively from a distinctively ethical approach. The aim of this article is to show that Confucius’ thought is a philosophy of life that can offer a valuable contribution to human culture. That is, Confucius does not present his thought as a potted ideology or a static doctrine, but above all as an “art of living”. In order to reconstruct the complexity of this philosophy, these pages analyze the notion of harmony (hé) from a comparative approach that blends Confucius’ thought and Dewey’s philosophy. Both of these traditions emphasize the importance of cultivating a harmonious and creative relationship with one’s surroundings, and the dialogue can offer benefits to present-day reflection.
Keywords: Confucianismo; Harmony; Aesthetic experience; Balance; Creativity